Echoes of Sorrow: Representations of Ritual Mourning in the Old Kingdom - Mendes Pinto, Joana (AUC Knowledge Fountain, 2026)
Given the number of mourning scenes found in Egyptian tombs, it is surprising that the origins of these rituals and the artistic conventions of their representations have rarely been the focus of study. Indeed, the majority of the literature relating to such scenes focuses on New Kingdom manifestations. This thesis maps the evolution of mourning scenes and relates it to concurrent religious and social changes occurring in Egyptian society from its inception in the Old Kingdom. By compiling all Old Kingdom scenes depicting mourners, this thesis sheds light on the emergence of this scene type in ancient Egyptian funerary representations and the role that it played in the tomb decoration and religious belief systems of the time. By compiling and analyzing the context in which these scenes are shown, this thesis identifies patterns of when, where and how this scene type was used. This is achived by looking at the geographical and diachronic distribution of these scenes as well as their location within the schema of decoration of the funerary monument (orientation, cardinal location, relationship to tomb shaft, statues, and to other related scenes). The gestures performed by the various mourner types across the difference scenes are also compiled and their evolution is analyzed across both time and geographical location (Memphite versus provincial representations).